“I’ve learned that I’m open-minded to this possibility”: A qualitative study to evaluate the acceptability of a psilocybin-aided smoking cessation treatment for people with HIV who smoke - Patricia A. Cioe; Garrett S. Stang; Danish Azam; Sarah Dugal (Addiction Science & Clinical Practice)
Abstract Background People with HIV (PWH) are disproportionately affected by cigarette use, with a 40 − 70% prevalence rate. Although many express a strong interest in quitting, many PWH who smoke experience lower cessation rates with traditional treatments, in part due to their comorbid anxiety and depressive symptoms. Psilocybin, a classic psychedelic referred to as “breakthrough therapy” by the U.S. Food & Drug Administration (FDA), has been shown to have potential as a therapeutic treatment for psychiatric symptoms, (e.g., anxiety and depression) and substance use disorders, including tobacco dependence. Preliminary evidence has shown that administering psilocybin to people who smoke and have been previously unable to quit with traditional treatments resulted in impressive smoking abstinence rates (80%) at 6-months in a smoking cessation pilot study. Objective Explore, using qualitative methods, the perceptions and acceptability of a psilocybin-assisted treatment for smoking cessation among PWH who smoke. Methods Semi-structured, in-depth qualitative interviews were conducted with PWH who smoke. Interviews were audio-recorded, transcribed verbatim, and analyzed using rapid thematic analysis. Results Twenty-five participants were enrolled: 15 cis male, 9 cis female, and 1 transgender female. Five main themes emerged: varying previous experiences with psilocybin; uncertainty about psilocybin’s effects and concern over potential side effects; need for trusted sources of information and testimonials; ultimately willing to try psilocybin-aided therapy for tobacco treatment; and, set and setting of psilocybin use matters. Conclusions Psilocybin-assisted smoking cessation treatment appears to be acceptable among PWH who smoke. Participants highlighted the importance of addressing key concerns related to an emerging therapy to increase acceptability and willingness to try it. Further research is needed to evaluate the safety and effectiveness of psilocybin prior to incorporating this emerging therapy for smoking cessation into tobacco treatment clinical services for PWH.